Sortal concepts and modality - Mackie, Penelope (University of Nottingham, 2013)
What is the modal significance of sortal concepts? It is generally accepted that sortal concepts provide persistence conditions with modal implications that are de re, and not merely de dicto. I do not think that this important assumption has received the scrutiny that it deserves. In this paper, I examine the contrast between a ‘pure de dicto’ theory of the persistence conditions associated with sortal concepts and a variety of de re theories, both essentialist and non-essentialist. I conclude that although there is a defensible argument against the pure de dicto theory, it has two interesting implications. First, the argument lends no support to an essentialist version of the de re theory. Secondly, it appears to support the rejection of the pure de dicto theory only by a theorist who is also a pluralist about coincidence. Hence it appears to provide no justification for the rejection of the pure de dicto theory on the part of a contingent identity theorist.